PENGOPTIMALAN SISTEM E-PROCUREMENT SEBAGAI LANGKAH PREVENTIF MEREDUKSI PERMASALAHAN DALAM PEKERJAAN KONSTRUKSI PENGADAAN BARANG/JASA PEMERINTAH - , Sulistiani, Anjar Sri Ciptorukmi Nugraheni (PRIVAT LAW II, 2016)
AbstractThis paperaimed to analyze the implementation of e-procurement system optimization as a preventive steps to reduce the high problems and frauds in the Construction Work Procurement of Governmentâs Goods/Services (PBJP).This research is a prescriptive normative legal research. Construction Work in PBJP subject to regulations related to e-procurement through Presidential Decree No. 4 of 2015 regarding Fourth Amendment Presidential Decree Number 54 Year 2010 concerning Procurement of Governmentâs Goods/Services (referred to as the Fourth Amendment of regulation PBJP). Results The study concluded that, based on the provisions of Article 106 paragraph (1) of the Fourth Amendment regulation PBJP mandated that in its implementation PBJP be conducted electronically with the loss of the terminology of the word